Anxiety Disorders Among Patients in Primary Care Centers - Hasan, Zainab Mohmmad Jawad; Lafta, Salam Fasal; Rasool, Ola Badri (Scientific Journal of Medical Research, 2025)
Objectives: To investigate the prevalence of anxiety disorders among patients presenting with somatic complaints in a primary care setting. Methods: A cross-sectional study was conducted on 106 patients attending a primary care unit. Participants completed self-report questionnaires assessing somatic and anxiety symptoms. Structured diagnostic interviews were conducted to confirm anxiety disorders. Results: Among 106 participants, the majority were young adults aged 26–35 (32.1%), with 66% being female. Approximately 83% of participants reported some level of anxiety. Income level was a significant predictor of anxiety, with lower-income individuals more likely to experience higher anxiety levels. Age, sex, marital status, and number of children were not significantly associated with anxiety. Conclusion: Anxiety disorders are highly prevalent among primary care patients with somatic complaints. These findings emphasize the need for routine anxiety screening and improved access to mental health services in primary care, particularly for low-income populations.